Derived Prepositions soobrazno and soobraznos ‘in accordance (with)’ as Indicators of Relations of Comparison - E. S. Sheremetyeva; T. Chuyeakayev (Научный диалог, 2017)
The article is devoted to the description of derived prepositions soobrazno ( s ) ‘in accordance (with)’ within a system of means of expression the relations of comparison. The research urgency is caused by necessity of systematization of the arsenal of service words, marking certain types of relationships, by identifying their belonging to the core or the periphery of the system. The novelty of this work lies in the object of study: these prepositions were not systematically analysed. The study of the functioning of prepositions is carried out in accordance with a methodology allowing to identify syntagmatic and semantic properties of prepositions. The focus of the study is the specificity of the compatibility of the mentioned prepositions. The result is that the syntagmatic properties of soobrazno and soobrazno s allow to consider them as formal variants. Results are presented of a comparative analysis of co-occurrence possibilities of the mentioned prepositions and prepositions within the core of means of expression of the relationship of conformity. The work concludes about the fundamental difference between the syntagmatic properties of prepositions soobrazno and soobrazno s and v sootvetstvii s and coincidence is revealed of the syntagmatic properties of analyzed in this work prepositions and preposition sootvetstvenno . In the result, the conclusion is made about the presence of semantic specificity of the prepositions of one semantic group.